2022
DOI: 10.3758/s13414-022-02610-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral asymmetries in visual short-term memory occur in retinotopic coordinates

Abstract: Visual short-term memory (VSTM) is an essential store that creates continuous representations from disjointed visual input. However, severe capacity limits exist, reflecting constraints in supporting brain networks. VSTM performance shows spatial biases predicted by asymmetries in the brain based upon the location of the remembered object. Visual representations are retinotopic, or relative to location of the representation on the retina. It therefore stands to reason that memory performance may also show reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies testing other aspects of visual perception have found mixed evidence for spatiotopic effects. Although some studies have found evidence of spatiotopic effects in visual memory, adaptation, and feature integration (Demeyer et al, 2009(Demeyer et al, , 2010(Demeyer et al, , 2011Ezzati et al, 2008;Fairhall et al, 2017;Fischer & Whitney, 2014;Harrison & Bex, 2014;Hayhoe et al, 1991;Melcher & Morrone, 2003;Mikellidou et al, 2021;Prime et al, 2006;Steinberg et al, 2022;Turi & Burr, 2012;Van Eccelpoel et al, 2008;Wijdenes et al, 2015;Wittenberg et al, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013), other studies only observed retinotopic evidence (Afraz & Cavanagh, 2009;Collins, 2019;Golomb et al, 2008;Golomb & Kanwisher, 2012a;Hui et al, 2020;McKyton et al, 2009;Shafer-Skelton et al, 2017;Shafer-Skelton & Golomb, 2018;Sheremata et al, 2023). As such, there has been a lot of debate over the years regarding reference frames for visual cognition across saccades (Cavanagh et al, 2010;Golomb & Mazer, 2021;Lappi, 2016;Marino & Mazer, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies testing other aspects of visual perception have found mixed evidence for spatiotopic effects. Although some studies have found evidence of spatiotopic effects in visual memory, adaptation, and feature integration (Demeyer et al, 2009(Demeyer et al, , 2010(Demeyer et al, , 2011Ezzati et al, 2008;Fairhall et al, 2017;Fischer & Whitney, 2014;Harrison & Bex, 2014;Hayhoe et al, 1991;Melcher & Morrone, 2003;Mikellidou et al, 2021;Prime et al, 2006;Steinberg et al, 2022;Turi & Burr, 2012;Van Eccelpoel et al, 2008;Wijdenes et al, 2015;Wittenberg et al, 2008;Wolfe & Whitney, 2015;Zimmermann et al, 2013), other studies only observed retinotopic evidence (Afraz & Cavanagh, 2009;Collins, 2019;Golomb et al, 2008;Golomb & Kanwisher, 2012a;Hui et al, 2020;McKyton et al, 2009;Shafer-Skelton et al, 2017;Shafer-Skelton & Golomb, 2018;Sheremata et al, 2023). As such, there has been a lot of debate over the years regarding reference frames for visual cognition across saccades (Cavanagh et al, 2010;Golomb & Mazer, 2021;Lappi, 2016;Marino & Mazer, 2016).…”
Section: Discussionmentioning
confidence: 99%